The Effect of ESG Performance on The Financial Performance of Manufacturing Companies Listed in The Indonesian - Barraq Mellina Zahroh; Hersugondo Hersugondo (AFEBI Management and Business Review, 2021)
This study was conducted to analyze the effect of environmental, social, and governance (environmental, social, and governance (ESG) performance on the company's financial performance. The company's financial performance is proxied by using Return On Assets. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2019 period. The sampling technique used purposive sampling to obtain a total of 13 manufacturing companies whose annual reports were published on idx.co.id and disclosed environmental, social, and governance scores on Bloomberg. The analytical method used is panel data regression using the E-views 9 program. The results of this study indicate that social performance, governance performance and ESG performance have a positive and significant effect on the company's financial performance while environmental performance has a negative and insignificant effect on the company's financial performance.Keywords: Environmental Performance, Social Performance, Governance Performance, ESG Performance, Financial Performance.